2022
DOI: 10.1111/nmo.14427
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa is a concern in gastroenterology: A scoping review

Abstract: There is concern that use of restrictive therapeutic diets, such as those used in disorders of the gut‐brain interaction (DGBI), may increase disordered eating. In this issue of Neurogastroenterology and Motility, Burton Murray et al. and Peters et al. both demonstrate a high prevalence of disordered eating in patients with gastrointestinal conditions, particularly those with DGBI. Given these findings, it is likely that orthorexia is common in this patient group, although this was not directly examined in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 118 publications
(297 reference statements)
2
16
0
Order By: Relevance
“…It is known that patients with T2DM have an increased risk of eating disorders. Although studies are limited, it is reported that the ON is also high in patients with T2DM [ 20 , 29 , 30 ]. We hypothesized that dieting may increase orthorexic behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that patients with T2DM have an increased risk of eating disorders. Although studies are limited, it is reported that the ON is also high in patients with T2DM [ 20 , 29 , 30 ]. We hypothesized that dieting may increase orthorexic behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies investigating the relationship between eating disorders and T2DM [16][17][18][19], our knowledge about the relationship between ON and T2DM is limited. When the relationship between chronic diseases and the prevalence of ON was examined, it was found that the highest prevalence was seen in T2DM [20] with 65.5% [21]. Despite this reported high prevalence of ON in patients with T2DM, neither the factors affecting ON in these patients nor their effects on diabetes self-management have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Orthorexia nervosa (an ED characterized by an obsessive and unsafe preoccupation with "clean" and healthy eating) is also observed in patients with IBD and irritable bowel syndrome. 5 EDs and DEBs may be underreported due to social desirability bias. 3 Many patients with IBD also adaptively restrict and/or over-restrict their diets due to disease symptoms and existing IBD ED research may overlook this nuance.…”
Section: The Sociocultural Aspects Of Diet and Body Imagementioning
confidence: 99%
“…Literature has demonstrated that patients with IBD have an increased risk of body image and eating issues: adolescents with IBD experience body image dissatisfaction (30%), disordered eating (10%), and avoidant restrictive food intake disorder (10%) 3,4 . Orthorexia nervosa (an ED characterized by an obsessive and unsafe preoccupation with “clean” and healthy eating) is also observed in patients with IBD and irritable bowel syndrome 5 . EDs and DEBs may be underreported due to social desirability bias 3 .…”
Section: The Sociocultural Aspects Of Diet and Body Imagementioning
confidence: 99%
“…There is increasing recognition of the importance of screening for and preventing the development of maladaptive dietary restriction in patients with DGBI as patients may develop orthorexia nervosa or avoidant/ restrictive food intake disorder (ARFID) [38]. The prevalence of ARFID in the older adult population has not been studied specifically but prevalence of disordered eating and ARFID ranges between 13 and 55% and 40% respectively in patients with DGBI [39,40].…”
Section: Diet-based Therapiesmentioning
confidence: 99%